If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2y + 13 = 14 + -1y Reorder the terms: 13 + -2y = 14 + -1y Solving 13 + -2y = 14 + -1y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add 'y' to each side of the equation. 13 + -2y + y = 14 + -1y + y Combine like terms: -2y + y = -1y 13 + -1y = 14 + -1y + y Combine like terms: -1y + y = 0 13 + -1y = 14 + 0 13 + -1y = 14 Add '-13' to each side of the equation. 13 + -13 + -1y = 14 + -13 Combine like terms: 13 + -13 = 0 0 + -1y = 14 + -13 -1y = 14 + -13 Combine like terms: 14 + -13 = 1 -1y = 1 Divide each side by '-1'. y = -1 Simplifying y = -1
| g(p+2)=3x^2+3x+1 | | -2-k=-8 | | -4c+18=5c | | (1/3)9squarred | | 7x+8-5x=-2 | | 7b+3=5b-11 | | -6+6x+7=(x+1)-2 | | -40-8=6s | | -2=0-1/5j | | 9-5a+a=-3 | | 6n-7(n-1)=12 | | 2m+6=2m-2 | | 5(z+6)=2+3z | | (6/5(p-4))-(6/5p) | | 0=16t^2+138t+55 | | 6a+2a+12=7+6a+3 | | 4x-5+2x=13 | | y=4x^2-6x-7 | | 0=16t^2+138t+c | | x^2-y^2=50 | | x+8+5x=2-2x | | 2x^3+7x^2-15=0 | | 7.6x-1.6=13.6 | | 2k=56 | | m-7m+6=20 | | -5k+3=-6+4k | | 6(k-3)-7=6k-(5k-2) | | x^2-x^2-2+1=7 | | 55r^2+28r-3= | | -y-2=11 | | 2(7x+3)+4=7(2x-1)+2x | | 7y/12-5=9-4y/3 |